CSIG-05. A GABP DOMINANT NEGATIVE APPROACH TO THE REVERSAL OF TUMOR IMMORTALITY. (14th November 2022) - Stevers, Nicholas; Collins, Sara; Kasahara, Noriyuki; Costello, Joseph F
Abstract: Immortality is a fundamental hallmark of human cancer cells and therapeutic reversal is of great interest. Telomerase Reverse Transcriptase promoter ( TERT p) mutations reactivate TERT expression, the rate limiting step in telomerase activity and cellular immortality. TERT p mutations are the most common non-coding mutation across all cancer types, including glioblastoma (GBM), oligodendroglioma, medulloblastoma, and high-grade meningioma. While prior telomerase therapies lack tumor selectivity and are poorly tolerated, TERT p mutations and their regulation offer a unique opportunity for tumor specific reversal of cellular immortality. The mutations generate a de novo E26 Transformation Specific (ETS) binding motif that recruits the GA-Binding Protein (GABP) multimeric complex to reactivate TERT expression. Initially we found a GABP tetramer reactivates the mutant TERT p, suggesting targeting only the tetramer may induce telomere shortening and tumor cell death. However, through knocking out this tetramer in cell cultures, we found that the GABP dimer is upregulated and maintains TERT expression. In the absence of both the dimer and one tetramer isoform, many tumor cells senesce or undergo cell death. However, some tumor cells escape this fate via upregulation of a second GABP tetrameric paralogue that maintains TERT expression. Therefore, to block all GABP complexes with a single approach, we devised a transactivation domain null, putative dominant negative GABP subunit that ultimately could be delivered to patients via a replicating retroviral system. Introduction of the construct into TERT p mutant glioma cells significantly reduced TERT expression while not altering expression in TERT p wildtype GBM cells, suggesting tumor selectivity. TERT expression was also reduced in a second TERT p mutant tumor type. We are currently investigating the long-term effects of the dominant negative GABP on telomere length and tumor immortality. Dominant negative GABP is a promising candidate for tumor selective reversal of cellular immortality by inhibiting mutant TERT p activation by all GABP multimeric forms.